Simple and Cost-effective Fabrication of a Supercapacitor Using Carbon Nanoparticle-based Ink - Alhebshi, Nuha A.; Aldosari, Nouf M.; Alsoulami, Wihad F.; Almehmadi, Ghada M.; Alzahrani, Raghad A. (Journal of King Abdulaziz University: Science, 2024)
The demand for energy storage devices such as supercapacitors is rapidly increasing in most applications, including electric transportation and portable electronics. The material’s high cost and the fabrication complexity of supercapacitors suppress their mass production. In this research, a commercial low-cost conductive ink has been simply painted on flexible stainless steel sheets as supercapacitor electrodes. The ink is mainly based on carbon crystals, as indicated by the X-ray diffraction peaks, and the results of the energy-dispersive X-ray spectroscopy confirm the elemental analysis. The carbon-based ink comprises semi-spherical nanoparticles as imaged by the scanning electron microscope. The electrochemical energy storage mechanism of the carbon nanoparticle-based electrode in the sulfuric acid electrolyte depends on the electric double layer, as investigated by the cyclic voltammetry and the galvanostatic charge-discharge measurements. As a result, the carbon ink-based supercapacitor exhibits a maximum areal capacitance of 0.5 mF/cm2 at 0.25 mA/cm2, a maximum energy of 0.2 µWh, and a maximum power of 1600 µW. The electrochemical impedance spectroscopy shows excellent equivalent series resistance of 0.6 ohm, representing a solid attachment of the ink on the stainless steel substrate. In addition, an angle of 45o in the low-frequency range indicates a semi-infinite diffusion of the electrolyte ions into the nanostructured electrodes. All these elemental, morphological, and electrochemical properties of the carbon-based ink promote its potential to be effortlessly implemented as electrodes, thereby contributing to the advancement of supercapacitor manufacture.